Machine learning approach for site classification - Brits, Laurence Armand (Stellenbosch : Stellenbosch University, 2025)
Brits, L. A. 2025. Machine Learning Approach for Site Classification. Unpublished doctoral dissertation. Stellenbosch: Stellenbosch University [online]. Available: https://scholar.sun.ac.za/items/36808931-50fc-4d14-aa7b-fec9c853fc75